Structural, Luminescence and Cytotoxicity Studies of PEG Capped CaS Nanophosphors. Issue 1 (1st January 2022) - Rekha, S; Aravind, S; Venkidesh, T V; Anila, E I
Abstract: Nanoparticles have remarkable applications in medical imaging and therapy owing to their enhanced optical, electronic, and structural properties. One of the challenges in nanoparticle application in the medical field is that when injected into the bloodstream, they are taken by the reticuloendothelial system (RES) of the body and removed by circulation. To avoid RES capture and protect them from the immune system, surface passivation of the nanoparticle is done with polyethylene glycol (PEG). The wet chemical synthesis of Calcium sulfide (CaS) nanophosphors capped with various concentrations of PEG is reported here. The structural and optical properties of the samples were studied by X-ray diffractogram (XRD), scanning electron microscopy (SEM), photoluminescence (PL) spectrum, and diffuse reflectance spectrum (DRS). The cell viability of the nanoparticles was estimated from the MTT assay using L929 human fibroblast cells. The cytotoxicity analysis revealed that PEG-capped CaS is biocompatible, which ensures the possibility of their prospective applications in the biomedical field.